Energetics of mixing and transport phenomena in Cd-X (X=Pb, Sn) melts - Koirala, R P; Koirala, I; Adhikari, D (BIBECHANA, 2017)
We report a quasi-chemical study of the thermodynamic and transport properties of mixing of liquid Cd-Pb and Cd-Sn alloys at 773K. The interaction energy in the alloys is found to be positive which suggests homo-coordination of atoms in the alloys. The viscosities of the alloys at 773K computed from two different approaches exhibit non-linear concentration dependence with the results for Cd-Sn alloy being in very good agreement and satisfactory agreement for Cd-Pb alloy. In lower concentrations of Cd-component, Cd-Pb alloy has larger viscosity and on the other side of concentration, Cd-Sn alloy has larger value. The calculations of inter-diffusion coefficients result in concave diffusion isotherms for the alloys. The higher values of inter-diffusion coefficients for Cd-Sn suggest that Cd and Sn metals tend to mix more readily than Cd and Pb metals do in Cd-Pb alloy. The correlation between viscosity and diffusion implies that the inter-diffusion coefficient is large for low viscous liquid alloy and vice-versa. BIBECHANA 15 (2018) 113-120